Un modelo de simulación de los flujos de migración interna de México : aplicación empírica de un modelo de interacción espacial - Garrocho, Carlos (El Colegio de México A.C., 1996)
In this paper spatial interaction theory is challenged in order to test if it is suitable to support the design and construction of an operative model of the Mexican internal migration flows. The main conceptual and operative aspects of the model are presented, the design and model building process is explained, the results of the calibration analysis are examined and a simulation exercise of migration policy evaluation is undertaken. The operative migration model presented in this paper seems useful to analyze and evaluate numerous migration policies, which suggest that spatial interaction theory offers a promising conceptual and operative foundation to analyze internal migration flows in Mexico.